Exploring services science: Third international conference, IESS 2012, Geneva, Switzerland, February 15-17, 2012. Proceedings - Snene, Mehdi (Lecture Notes in Business Information Processing, 2012)
This book contains the refereed proceedings of the Third International Conference on Exploring Services Science (IESS) that was held in Geneva, Switzerland, in February 2012.At the conference, researchers from all over the world present innovative ideas, research, and applications in the design, management, and evaluation of services. This year, the main theme was the interdisciplinary aspect of services. The 22 full papers accepted for IESS were selected from 46 submissions and presented ideas and results related to innovation, services discovery, services engineering, and services management as well as the application of services in information technology, businesses, e-learning and public administration.